Desarrollo histórico del barrio brazales a través de la oralidad de sus moradores - Cofre Chango, Lilia Mariana (2016)
The oral tradition is as old as the existence of the humanity which allows expressing cultural events; the stories, narrations, tales, legends, histories from memory to memory, are particular ways that allow people expressing their legacy. The oral tradition that has not been appreciated at the time, has died with its town losing the collective wisdom. Writing is a way to capture the legacy of orality in a lasting text. The purpose of the research was to rescue the orality which comes from the older adults….